A Cross Sectional Survey for Dermatoses in Children and Adolescents Residing in Orphanages in Urban Tirunelveli, Tamil Nadu, India - Nirmaladevi Palanivel; Vijaikumar Manikka Govardhanan; Soundharyaa Savada Moorthi; A N. M. Maalik Babu; S M Kannan (Indian Journal of Dermatology, 2021)
Context: Skin diseases are a major cause of public concern among underprivileged people residing in orphanages. There is a need for community-based study for dermatoses in orphanages as the literature is scarce at the national and international levels. Aims: For profiling of various dermatoses to generate information on general health, nutritional status, and sanitation, and to educate about personal skin hygiene and care to inmates in urban child orphanages. Settings and Design: A cross-sectional study was conducted at 18 urban child orphanages in Tirunelveli city for 1 month. Methods and Material: A predesigned proforma was prepared and the demographic details regarding the inmates were obtained and they were screened under natural light for skin, hair, nail, and oral disorders as well as their built, nourishment, height, and weight were measured and recorded in tabulations. Statistical Analysis Used: Descriptive statistical analysis was followed for describing the prevalence of dermatoses and the age group affected which are explained in percentages and ratios. Results: Out of a total of 850 inmates, 93 (11%) were of 5–9 years and 757 (89%) were of 10–19 years. Among them, 330 (39%) were males and 520 (61%) were females. Overall, the inmates affected with dermatoses were 360 (42.4%) and infectious dermatoses were seen in 218 inmates (60.5%) and non-infectious dermatoses were seen in 142 inmates (39.5%). Adolescent females were more commonly affected and the commonest dermatoses observed were pediculosis capitis (13.6%) followed by acne vulgaris (8.1%) and in adolescent males, scabies (7.1%) was the commonest. No psychocutaneous disorders were encountered. Conclusions: Infections and infestations are common in orphanages due to a lack of awareness of personal hygiene and self-care practices. They should be given health education in order to reduce the disease burden in children living in orphanages which in turn decreases the disease burden at the community level.